Investigating the trustworthiness of research evidence used to inform public health policy: a qualitative interview study on the use of predatory journal citations in policy documents - Marc A. Albert; Manoj M. Lalu; Agnes Grudniewicz (Health Research Policy and Systems)
Abstract Evidence-based policymaking has increased policymakers’ capacity to make scientifically informed health policy decisions. However, reaping the benefits of this approach requires avoiding untrustworthy research – potential sources of which are predatory journals. In this study, we sought to understand how research cited in policy documents is sourced and evaluated, and identify factors that may be contributing to the citation of predatory journals or other less trustworthy evidence. To this end, we conducted semi-structured interviews with individuals who have prepared public health policy documents. These interviews were thematically analysed, and five key overarching themes were generated regarding the process of deciding how to develop policy documents (e.g. which individuals to involve) and how this may impact which information is included; obstacles such as limited evidence that may hinder policy document development; and concerns around transparency throughout the development process. Our findings highlight that in many cases, information cited in policy documents is sourced and evaluated with variable rigour. This may contribute to the citation of untrustworthy research in policy documents. Certain steps can be taken to help minimize any potential negative impact of relying on such sources (e.g. improving transparency), but a better understanding of policymakers’ perspectives regarding how taking these steps would impact their decision-making process may be required to ensure successful implementation.